INFORMATION SECURITY AS A COMPONENT OF THE NATIONAL SECURITY OF UKRAINE - Младьонова, О. Д. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
Information security is analyzed as a component of Ukraine's national security. National interestis a combination of the needs of the state, society, and man. It is concluded that security is the resultof managing potential or real threats and dangers and is aimed at satisfying the national interests ofthe state, society, and man. The existence and development of the state are maintained through theproper functioning of the relevant state and legal institutions.